ANALISIS TINGKAT PENGETAHUAN MASYARAKAT TERHADAP PEMANFAATAN AIR TANAH DI GAMPONG LENGKONG KECAMATAN LANGSA BARO - Sabri Sabri; Faiz Urfan (Geography Education Study Program, Universitas Samudra, 2022)
Groundwater is water in which this form of groundwater is found in the soil around our earth. Groundwater is also a source of clean water. Gampong Lengkong is a village located in Langsa Baro District, Langsa City. In general, the climate is hot and rainy, the hydrological conditions have a lot of storing aquifers, namely groundwater resources, so that this area appears many springs from small scale to large discharge scale which indicates the existence of groundwater sources. Community knowledge about the use of ground water is ground water that is not managed by the community properly. Exploitation of groundwater is one of the water that cannot be controlled properly so that the impact can have a negative impact on the ground water balance. Conservation is the community's need to have sufficient groundwater in the future. Groundwater management strategies need to be considered so that capacity in managing can have the main task in licensing the groundwater management strategy. This study aims to analyze the level of community knowledge about groundwater conditions, the level of community knowledge about the impact of groundwater exploitation, and analyze the level of community knowledge about groundwater conservation in Lengkong Village, Langsa Baro District.